Optogenetic confirmation of transverse-tubular membrane excitability in intact cardiac myocytes - Scardigli, Marina; Pásek, Michal; Santini, Lorenzo; Palandri, Chiara; Conti, Emilia; Crocini, Claudia; Campione, Marina; Loew, Leslie M; de Vries, Antoine A F; Pijnappels, Daniël A; Pavone, Francesco S; Poggesi, Corrado; et al. (Journal of physiology (London. Print), 2024)
T-tubules (TT) form a complex network of sarcolemmal membrane invaginations, essential for well-co-ordinated excitation-contraction coupling (ECC) and thus homogeneous mechanical activation of cardiomyocytes. ECC is initiated by rapid depolarization of the sarcolemmal membrane. Whether TT membrane depolarization is active (local generation of action potentials; AP) or passive (following depolarization of the outer cell surface sarcolemma; SS) has not been experimentally validated in cardiomyocytes. Based on the assessment of ion flux pathways needed for AP generation, we hypothesize that TT are excitable. We therefore explored TT excitability experimentally, using an all-optical approach to stimulate and record trans-membrane potential changes in TT that were structurally disconnected, and hence electrically insulated, from the SS membrane by transient osmotic shock. Our results establish that cardiomyocyte TT can generate AP. These AP show electrical features that differ substantially from those observed in SS, consistent with differences in the density of ion channels and transporters in the two different membrane domains. We propose that TT-generated AP represent a safety mechanism for TT AP propagation and ECC, which may be particularly relevant in pathophysiological settings where morpho-functional changes reduce the electrical connectivity between SS and TT membranes. KEY POINTS: Cardiomyocytes are characterized by a complex network of membrane invaginations (the T-tubular system) that propagate action potentials to the core of the cell, causing uniform excitation-contraction coupling across the cell. In the present study, we investigated whether the T-tubular system is able to generate action potentials autonomously, rather than following depolarization of the outer cell surface sarcolemma. For this purpose, we developed a fully optical platform to probe and manipulate the electrical dynamics of subcellular membrane domains. Our findings demonstrate that T-tubules are intrinsically excitable, revealing distinct characteristics of self-generated T-tubular action potentials. This active electrical capability would protect cells from voltage drops potentially occurring within the T-tubular network.
Keywords: buněčná membrána; membránové potenciály; kardiomyocyty; Membrane Potentials; akční potenciály; sarkolema; optogenetika; Action Potentials; Myocytes, Cardiac; Optogenetics; Cell Membrane; Sarcolemma